2017
DOI: 10.1515/foecol-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Immission-load-related dynamics of S-SO4 2− in precipitation and in lysimetric solutions penetrating through beech ecosystems

Abstract: Kukla, J., Bublinec, E., Schieber, B., Kellerová, D., Bičárová S., Janík, R., 2017. Immission-load-related dynamics of S-SO 4 2-in precipitation and in lysimetric solutions penetrating through beech ecosystems. Folia Oecologica, 44: 96-106.The paper presents the results of a 23-year study of sulphate sulphur dynamics in beech ecosystems exposed to different immission loads. . The S-SO 4 -2 amounts penetrating the individual soil layers in the Kremnické vrchy Mts were as follows: in case of surface humus on cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The analysed material consisted of 30 shoots from each site (n = 30; 15 terminal shoots -stems and 15 lateral shoots -branches). Supplementary information on the research sites can be found in Barna (2015), Gašová et al (2017), and Kukla et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…The analysed material consisted of 30 shoots from each site (n = 30; 15 terminal shoots -stems and 15 lateral shoots -branches). Supplementary information on the research sites can be found in Barna (2015), Gašová et al (2017), and Kukla et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…This area is characterised by its volcanic origin, andesite bedrock, and stony andosol soil. The stone content is 30-40% on average and increases with soil depth [19]. The research site is situated on a west-oriented aspect with 20% slope and altitude range between 450 and 510 m a.s.l.…”
Section: Site and Stand Conditionsmentioning
confidence: 99%
“…This study was conducted in three localities ( Table 1) within submontane beech forests of the Western Carpathians (Central Europe, Central Slovakia). The Žiar locality is situated in the Štiavnické vrchy Mountains, located 1.5 km from an aluminium plant in Žiar nad Hronom; it was formerly under the immediate influence of pollutants, acidic fluorine-type emissions in the zone of pollutant threat A [25]. Since 1996, when a new modern plant with significantly reduced emissions began its operation, pollutant emissions from the aluminium plant have been significantly reduced ( Table 2).…”
Section: Study Areamentioning
confidence: 99%